Iron metabolism and innate immunity - Ganz, Tomas (Henry Stewart Talks, 2009)
Iron is an essential element for nearly all infectious microorganisms as well as for their plant and animal hosts, Within hours of infection, animals sequester iron within macrophages as well as in specialized extracellular proteins, The cellular component of this response causes a marked decrease in extracellular iron concentration, Hepcidin is a recently characterized peptide that functions as the homeostatic iron-regulatory hormone and as the mediator of inflammatory iron sequestration, It acts by binding to the sole known cellular iron exporter, ferroportin, and inducing its internalization and degradation, Pathological regulation or dysregulation of the hepcidin-ferroportin axis is responsible for a number of common iron-related disorders including anemia of inflammation, hereditary hemochromatosis and iron-loading anemias, Update interview: Structural basis of the hepcidin-ferroportin interaction, Update interview: Changes in iron status transcriptionally regulate hepcidin through the bone morphogenetic protein receptor (BMPR) pathway, Update interview: BMP2 and BMP6 as the key ligands, Update interview: Hepcidin synthesis is prominently modulated by erythropoiesis through erythroferrone, Update interview: Iron is essential for clonal expansion of lymphocytes, Update interview: Severe restriction of iron availability can be immunosuppressive
Updated at 2020/07/08